The Effect of Metacognitive Monitoring Strategy on Improving English Listening Comprehension among Tenth Graders in North Eastern Badiah Directorate - Alshurafat, Ziad Salem; Alkhawaldeh, Ahmad Hamad (Dirasat: Educational Sciences, 2020)
This study aims at exploring the effect of metacognitive monitoring strategy of instruction on developing English listening comprehension among tenth graders in North Eastern Badiah directorate. The study used a quasi-experimental design. The sample of the study consisted of 123 male and female students who were intentionally chosen from four schools. Experimental and control groups were assigned randomly. The groups of the study were found equivalent upon analyzing students’ scores on a listening comprehension test using Two-way ANCOVA. The experimental group was instructed using metacognitive monitoring program, whereas students of the control group were taught in a conventional way. A jury of judges was invited to comment on a listening test and an instructional program to establish their validity. The findings of the study revealed that there were statistically significant differences at (α =0.05) between students’ total achievement of the experimental and the control groups in the listening comprehension in favor of the experimental group. In the light of the findings, the researcher provides some recommendations to the Jordanian Ministry of Education and TEFL educators.